Employee retention and organizational performance in Kabale District Local Government, Uganda - Fabian Mwosi; Marus Eton; Simon Peter Olupot; Bernard Patrick Ogwel (goodwood publishing, 2024)
Purpose: This study investigates the connection between Kabale District Local Government (KLDG) staff retention and organizational performance. Research Methodology: A correlational study design with the goal of reporting on the connection between staff retention and organizational performance in the local government of the Kabale District. A sample size of 96 respondents was chosen from among the 142 division personnel and staff in the sub-counties that participated in the survey. A survey consisting of questionnaires and interviews was conducted to gather data. Results: The degree and intensity of the association between employee retention and organizational performance were determined using a correlation analysis. Qualitative data derived from interviews were documented and categorized verbatim. When the influence of the work environment was considered, the study discovered a very weak link between employee retention and organizational performance. Limitations: This study was conducted to cover employee retention and employee performance in one district, and the results cannot be generalized. Contribution: The study suggests that the Kabale District Local Government (KCLG) needs to make improvements to its workplace to encourage staff members to remain with the institution. The district should follow established protocols, including local government, public financial management, and public service standing orders. An independent investigation of the contribution of policy execution to the achievement of organizational objectives in Ugandan local governments is also warranted.